Chronic pain is common in mitochondrial disease - van den Ameele, Jelle; Fuge, Joshua; Pitceathly, Robert D.S.; Berry, Sarah; McIntyre, Zoe; Hanna, Michael G.; Lee, Michael; Chinnery, Patrick F. (Neuromuscular disorders : NMD, 2020)
•Chronic pain is common in patients with mitochondrial disease.•Pain due to mitochondrial disease is primarily of neuropathic nature.•Distribution, intensity and type of pain are genetically determined. In the absence of cure, the main objectives in the management of patients with mitochondrial disease are symptom control and prevention of complications. While pain is a complicating symptom in many chronic diseases and is known to have a clear impact on quality of life, its prevalence and severity in people with mitochondrial disease is unknown. We conducted a survey of pain symptoms in patients with genetically confirmed mitochondrial disease from two UK mitochondrial disease specialist centres. The majority (66.7%) of patients had chronic pain which was primarily of neuropathic nature. Presence of pain did not significantly impact overall quality of life. The m.3243A>G MTTL1 mutation was associated with higher pain severity and increased the likelihood of neuropathic pain compared to other causative nuclear and mitochondrial gene mutations. Although previously not considered a core symptom in people with mitochondrial disease, pain is a common clinical manifestation, frequently of neuropathic nature, and influenced by genotype. Therefore, pain-related symptoms should be carefully characterised and actively managed in this patient population.